Hubungan antara Coping terkait Stres Sekolah dan Persepsi Keterlibatan Orangtua pada Remaja - Namira Insyiranda; Airin Yustikarini Saleh (Jurnal Ilmiah Psikologi MIND SET, 2018)
Applying functional coping when dealing with school-related problems is very important that can be benefical to make a good academic performance at the school. There are several factors that can affect the use of coping in adolescents. Parental involvement was assumed can predict the use of coping in adolescents. The aim of this study is to examine the relationship between parental involvement that perceived by students and coping with school-related stress in adolescence. Participants of this study was 405 adolescents in third grade of high school from eight different schools. Perceived parental involvement was measured in two version for father and mother, using Reported Father Involvement Scale (Finley & Schwartz, 2004) and Reported Mother Involvement Scale (Finley, Mira, & Schwartz, 2008). Coping with school-related stress was measured by Coping Accross Situational Questionnaire-Revised (Barnes, 2011). The result showed that there are significant relationship between two types of coping style, that were active coping and internal coping with both perceived father involement and perceived mother involvement.